The role of the South African Democratic Teachers Union in the process of teacher rationalisation in the Western Cape between 1990 and 2001 - Nkomo, Mokubung O. (University of Pretoria, 2013)
Thesis (PhD (Education Policy Studies))--University of Pretoria, 2008.